QADRIYATLAR NAMOYON BOʻLISHINING PSIXOLOGIK XUSUSIYATLARI - Kurbaniyozova, R.Y. (SCIENCE and SOCIETY, 2024)
The article reveals the characteristics of the concept of values. Values are considered as the main category of a person’s life. Knowledge is given about how a person perceives situations through the value system and reacts to the external environment based on this.